Analysis of suffusion in cohesionless soils with randomly distributed porosity and fines content. (July 2019) - Yang, Jie; Yin, Zhen-Yu; Laouafa, Farid; Hicher, Pierre-Yves
Abstract: Suffusion occurs when fines are plucked off by seepage forces and transported throughout the pores of the matrix constituted by coarser soil particles. Natural or human made soils are seldom homogeneous, which makes suffusion more complex. Suffusion is usually combined with the self-filtration of the fine particles and the transport of these fines may cause the soil structure to become looser. At the same time a clogging may occur which could reduce the permeability leading to an increase of excess pore pressure. The combination of these two phenomena will result in strength degradation. Currently, most suffusion analyses are performed without taking into account the soil's spatial variability. In this paper, a four-constituent continuum finite difference model for suffusion has been extended through the self-filtration process. A random field theory was at this point introduced into the finite difference code to investigate soil suffusion with a randomly distributed initial porosity and fines content. A probabilistic study using the Monte Carlo method was conducted to analyze the effect of the variance, the spatial correlation length, and the cross correlation of the randomly distributed initial porosity and fines content on the eroded mass and on the evolution of the hydraulic conductivity under 1D and 2D conditions. Based on all the simulations, it was possible to quantify the probability of particle blockage during erosion.